Information seeking behaviour in the digital environment - Furi, Ivana (Knjižnica, 2016)
Purpose: The paper presents selected findings of a small-scale pilot study on the actual information-seeking behaviour of the Osijek University students in the digital environment. Design/Methodology/Approach: A qualitative research was conducted on the sample of six graduate students of different social science disciplines (information sciences, psychology, economy, cultural management) who were asked to perform searches in order to provide answers to several information tasks. The research method used in the research was a think-aloud method where the respondents were asked to verbalise their thoughts and feelings while performing the simulated search tasks. The respondents were video-recorded and the transcripts of video material were subsequently analysed and interpreted. Research limitations: The small and convenient sample limits the findings. Originality/Value: The results provide the useful insight into the information behaviour of students in the electronic environment (their search strategy, search steps, feelings, etc.) but surprisingly reveals the poor information seeking skills of information-science students.
Keywords: digital environment; students; študenti; information seeking behaviour; student; University of Osijek; informacijsko vedenje; digitalno okolje; Univerza v Osijeku